Plasticized Cmc-ammonium Acetate Based Solid Biopolymer Electrolyte: Ionic Conductivity And Transport Study - Mohd Ibnu Haikal Ahmad Sohaimy; Nurul Izzati Zainuddin; Mohd Ikmar Nizam Mohamad Isa (UMT, 2024)
Indexed by SCOPUS/ERA/MYCITE